Analysis of racism depicted in Octavia E. Butler’s Kindred novel - Sherina Ananda Priyadi; Taufiq Effendi (LADU: Journal of Languages and Education, 2022)
Background: This research analyzes forms of racism experienced by Edana Franklin in the novel entitled Kindred by Octavia E. Butler. Purpose: The intent of the research is to discover the forms of racism encountered by Edana Franklin, as the main character of the novel. Design and methods: The method that is used is descriptive qualitative method. The source data is Edana Franklin’s experiences of slavery/racism conduct in the novel written by Octavia E. Butler. The researcher uses Henry and Tator forms of racism theory, secluded by four forms which are: Internalized Racism, Interpersonal Racism, Institutional Racism, and Structural Racism to define the racism depicted in the novel “Kindred”. Results: After analyzing Kindred, the researcher found an amount of forms of racism. The first one is Internalized Racism five (5) data, Interpersonal Racism twenty-three (23) data, Institutional Racism six (6) data, Structural Racism twenty (20) data. Resulting to the total of fifty-four (54) data in total.